Revista Latinoamericana de Derechos Humanos: 20 años - Cerdas Agüero, Evelyn (2020)
This paper aims to review 20 years of history of the Revista Latinoamericana de Derechos Humanos (Latin American Journal of Human Rights) since its inception as DEHUIDELA in 2009.  The article proposes that this publication is born as an effort of the Instituto de Estudios Latinoamericanos (Institute of Latin American Studies) (IDELA) to support the Human Rights program, as well as an opportunity to develop various themes that will stimulate the students of the Institute in their research topics.  Starting with a new effort in 2009, the journal takes a step to become an indexed scientific publication whose main focus is the publication of works related to human rights as perceived from various disciplines and approaches.  It is concluded  that the work input over the years has made Revista Latinoamericana de Derechos Humanos a quality print and electronic publication that contributes to the dissemination of knowledge of human rights in Latin America from the public university.es